Improving Early Childhood Expressive Language Skills through Local Wisdom-Based Singing Methods at Pertiwi IXE Tebo Kindergarten: Peningkatan Kemampuan Bahasa Ekspresif Anak Usia Dini melalui Metode Bernyanyi Berbasis Kearifan Lokal di TK Pertiwi IXE Tebo - Kasiatun (Journal of Vocational Education and Information Technology (JVEIT), 2026)
Expressive language skills are fundamental for early childhood communication, social interaction, and cognitive development. However, excessive gadget exposure and the erosion of local cultural values have led to a decline in children's expressive language abilities. This study aims to improve the expressive language skills of early childhood through a singing method based on local wisdom at TK Pertiwi IXE Tebo, Jambi. This research employs Classroom Action Research (PTK) using the Kemmis and McTaggart model, conducted in two cycles. The subjects were 18 children (9 boys and 9 girls) aged 5-6 years in Group B. Data collection techniques included observation, documentation, field notes, and unstructured interviews, analyzed using descriptive qualitative and quantitative methods. The results showed a significant improvement in children's expressive language skills. In the pre-cycle, only 27.8% of children reached the expected developmental milestones (BSH/BSB). This increased to 61.1% in Cycle I and reached 88.9% in Cycle II. The singing method based on Jambi local wisdom, featuring modified traditional songs such as 'Injit-injit Semut', 'Selendang Mayang', 'Pinang Muda', and 'Seloko Melayu Jambi', successfully enhanced children's vocabulary, sentence construction, articulation, storytelling ability, and question-answer skills. The study concludes that a singing method based on local wisdom is an effective pedagogical intervention for improving early childhood expressive language skills while preserving cultural heritage.